Responding to Climate Policy Risk Through the Dynamic Role of Green Innovation: Evidence from Carbon Information Disclosure in Emerging Markets - Runyu Liu; Mara Ridhuan Che Abdul Rahman; Ainul Huda Jamil (Risks)
This study investigates how firms in emerging markets respond to climate policy risk, with a particular focus on the dynamic role of green innovation in shaping carbon information disclosure. Using a difference-in-differences (DID) framework, we examine the impact of China’s 2018 carbon reporting policy, which represents an institutionally significant but non-mandatory regulatory intervention, on the disclosure behaviors of A-share listed firms from 2013 to 2022. The results show that the policy significantly increased firms’ attention to carbon information disclosure, especially among those with limited green innovation capacity. In contrast, firms with stronger innovation capabilities exhibited more stable disclosure practices, suggesting a buffering effect against regulatory uncertainty. Further analysis reveals that the moderating effect of green innovation changes over time, as innovation-oriented firms gradually adjust their disclosure strategies in response to evolving policy expectations. These findings highlight green innovation as a key internal resource that enables firms to strategically adapt to climate policy risks. This study contributes to the literature on climate risk management and corporate sustainability by providing empirical evidence on how dynamic capabilities shape disclosure outcomes and risk management strategies under changing regulatory conditions.